Advanced Security Threats and Mitigation Techniques in Virtualized Environment - Ramakrishnan, N.; Subbulakshmi.T, Dr. (International Journal of Engineering and Technology, 2019)
â€˜Virtualizationâ€™ is not the new buzzword in IT field as it was introduced in 1960s by IBM while trying providing solution to accommodate multiple users over expensive computer resources with time shared solutions.This solution supported every technology and protocols of physical computer infrastructure. Even though it kept evolving over the years, the technology achieved its reach with the introduction of VMware workstation by VMware Company in year 1999.At present there are enough solutions available to virtualize our computer resources.However the rush seen in embracing this technology has not been justified when we consider the security issues attached to it. Virtualization by itself is considered erroneously as a security solution. In fact it increases the attack surface area, along with the more probability of successful execution of various cyber-attacks. This paper is intended to study in detail about the advanced threats and their mitigation techniques that are to be understood while operating in virtualized environment. Â Â